Ultrastructural findings in autosomal dominant drusen - Holz, Frank G.; Owens, Sarah L.; Marks, James; Haimovici, Robert; Bird, Alan C. (Archives of ophthalmology, 1997)
We report the electron microscopic findings in a patient with autosomal dominant drusen. The clinical features of the drusen resembled those occurring in age-related macular degeneration and were different from other dominantly inherited drusen syndromes, including malattia leventinese and Doyne honeycomb familial choroiditis. The predominant ultrastructural features included deposition of material between the basement membrane of the retinal pigment epithelium and inner collagenous layer of the Bruch membrane, which was composed of membranous material, tubelike structures, and vesicles. These ultrastructural findings were similar to those found in aging, implying that this autosomal dominant macular degeneration may represent a homologue of age-related macular degeneration.
Gesehen am 24.11.2025